Disease-specific oligodendrocyte lineage cells arise in multiple sclerosis. (December 2018) - Falcão, Ana; Bruggen, David; Marques, Sueli; Meijer, Mandy; Jäkel, Sarah; Agirre, Eneritz; Samudyata,; Floriddia, Elisa; Vanichkina, Darya; ffrench-Constant, Charles; Williams, Anna; Guerreiro-Cacais, André; et al.
Abstract Multiple sclerosis (MS) is characterized by an immune system attack targeting myelin, which is produced by oligodendrocytes (OLs). We performed single-cell transcriptomic analysis of OL lineage cells from the spinal cord of mice induced with experimental autoimmune encephalomyelitis (EAE), which mimics several aspects of MS. We found unique OLs and OL precursor cells (OPCs) in EAE and uncovered several genes specifically alternatively spliced in these cells. Surprisingly, EAE-specific OL lineage populations expressed genes involved in antigen processing and presentation via major histocompatibility complex class I and II (MHC-I and -II), and in immunoprotection, suggesting alternative functions of these cells in a disease context. Importantly, we found that disease-specific oligodendroglia are also present in human MS brains and that a substantial number of genes known to be susceptibility genes for MS, so far mainly associated with immune cells, are expressed in the OL lineage cells. Finally, we demonstrate that OPCs can phagocytose and that MHC-II-expressing OPCs can activate memory and effector CD4-positive T cells. Our results suggest that OLs and OPCs are not passive targets but instead active immunomodulators in MS. The disease-specific OL lineage cells, for which we identify several biomarkers, may represent novel direct targets for immunomodulatory therapeutic approaches in MS. Single-cell RNA-seq of a mouse model of multiple sclerosis uncovers new oligodendrocyte populations and putative disease markers and suggests new mechanisms underlying the pathogenesis of the disease.